2021
DOI: 10.1123/ijspp.2020-0887
|View full text |Cite
|
Sign up to set email alerts
|

Is a Head-Worn Inertial Sensor a Valid Tool to Monitor Swimming?

Abstract: Purpose: This study aimed to independently validate a wearable inertial sensor designed to monitor training and performance metrics in swimmers. Methods: A total of 4 male (21 [4] y, 1 national and 3 international) and 6 female (22 [3] y, 1 national and 5 international) swimmers completed 15 training sessions in an outdoor 50-m pool. Swimmers were fitted with a wearable device (TritonWear, 9-axis inertial measurement unit with triaxial accelerometer, gyroscope, and magnetometer), placed under the swim cap on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…Table 2 summarizes the aims of the studies, the participants´ demographics, and the swim strokes. From the 18 articles included for qualitative synthesis, eight (44.4%) [ 21 , 23 , 24 , 25 , 30 , 31 , 34 , 38 ] assessed wearables exclusively in front crawl, six (33.3%) [ 26 , 27 , 29 , 32 , 33 , 35 ] assessed wearables exclusively in all four swim strokes, two assessed wearables for the tumble turn in front crawl (11.1%) [ 36 , 37 ], one just assessed wearables in breaststroke (5.5%) [ 22 ], and another one assessed wearables in butterfly stroke (5.5%) [ 28 ]. Overall, 177 swimmers were recruited in all studies (103 males, 62 females, and 12 that the authors failed to note the sex of the participants).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 summarizes the aims of the studies, the participants´ demographics, and the swim strokes. From the 18 articles included for qualitative synthesis, eight (44.4%) [ 21 , 23 , 24 , 25 , 30 , 31 , 34 , 38 ] assessed wearables exclusively in front crawl, six (33.3%) [ 26 , 27 , 29 , 32 , 33 , 35 ] assessed wearables exclusively in all four swim strokes, two assessed wearables for the tumble turn in front crawl (11.1%) [ 36 , 37 ], one just assessed wearables in breaststroke (5.5%) [ 22 ], and another one assessed wearables in butterfly stroke (5.5%) [ 28 ]. Overall, 177 swimmers were recruited in all studies (103 males, 62 females, and 12 that the authors failed to note the sex of the participants).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 177 swimmers were recruited in all studies (103 males, 62 females, and 12 that the authors failed to note the sex of the participants). Four articles recruited elite-level swimmers (22.2%) [ 29 , 32 , 34 , 37 ], two articles recruited international-level participants (11.1%) [ 33 , 35 ], four articles recruited national-level/semi-professional participants (22.2%) [ 22 , 28 , 35 , 38 ], one article recruited local-level participants (5.5%) [ 31 ], and three articles recruited local/non-expert swimmers (16.7%) [ 22 , 25 , 36 ]. Conversely, six articles (33.3%) [ 21 , 23 , 24 , 26 , 27 , 30 ] did not report the swimmers’ competitive level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensor location on the head had several advantages, as it did not affect drag, and measured overall body motion. For this reason, this location was used to estimate the stroke parameters or intracyclic velocity of the swimmer [29,30]. Nevertheless, Shell et al found the accuracy of stroke parameter estimation was not sufficient enough for the training monitoring tool [29].…”
Section: Introductionmentioning
confidence: 99%